Weekends with Max and his dad - Urban, Linda (Houghton Mifflin Harcourt, 2016)
Third-grader Max pursues neighborhood adventures with his dad as they both adjust to recent changes in their family
Keywords: JUVENILE FICTION / Family / Marriage & Divorce / bisacsh; JUVENILE FICTION / Boys & Men / bisacsh; JUVENILE FICTION / Imagination & Play / bisacsh; JUVENILE FICTION / Lifestyles / City & Town Life / bisacsh; Fathers and sons; Neighborhoods; Divorce; JUVENILE FICTION / Family / Marriage & Divorce; JUVENILE FICTION / Boys & Men; JUVENILE FICTION / Imagination & Play; JUVENILE FICTION / Lifestyles / City & Town Life; Kinderbuch